Transforming Growth Factor-β and Long Non-coding RNA in Renal Inflammation and Fibrosis - Gu, Yue-Yu; Dou, Jing-Yun; Huang, Xiao-Ru; Liu, Xu-Sheng; Lan, Hui-Yao (Frontiers in Physiology, 2021)
Renal fibrosis is one of the most characterized pathological features in chronic kidney disease (CKD). Progressive fibrosis eventually leads to renal failure, leaving dialysis or allograft transplantation the only clinical options for CKD patients. Transforming growth factor-β (TGF-β) is not only the key mediator in renal fibrosis but also is an essential regulator for renal inflammation. Therefore, the general blockade of the pro-fibrotic TGF-β may reduce fibrosis but may risk promoting renal inflammation and other side effects due to the diverse role of TGF-β in kidney diseases. Long non-coding RNAs (lncRNAs) are a group of RNA transcripts that are more than 200 nucleotides and have been regarded as promising therapeutic targets for many diseases. In this review, we are focusing on the importance of TGF-β and lncRNAs in renal inflammation and fibrogenesis, and the potential applications of TGF- and lncRNAs as the therapeutic targets or biomarkers in renal fibrosis and CKD are highlighted.